Comparing Robotic Surgery With Conventional Laparoscopy and Laparotomy for Cervical Cancer Management. Issue 6 (1st July 2014) - Chen, Ching-Hui; Chiu, Li-Hsuan; Chang, Ching-Wen; Yen, Yuan-Kuei; Huang, Yan-Hua; Liu, Wei-Min
Abstract : Objective: The aim of this study was to compare the outcomes of robotic surgery, laparoscopy, and laparotomy for the surgical treatment of stage IA to IIB cervical cancer. Methods: This retrospective study was carried out in a university-affiliated teaching hospital. A total of 100 women with an initial diagnosis of stage IA to IIB cervical cancer, without preoperative brachytherapy or chemotherapy, were included in this study. With selection of the cases, 44 patients received laparotomy surgery, 32 patients received laparoscopic surgery, and 24 patients received robotic surgery. The perioperative parameters measured included operation time, blood loss, transfusion rate, lymph node yield, adhesion score, laparotomy conversion rate, postoperative and 24-hour pain scores, time to full diet resumption, and hospital stay. The perioperative complication and disease-free survival were also evaluated. Results: The robotic group showed a shorter operation time, less blood loss, lower transfusion rate, and lower laparotomy conversion rate than the laparoscopic or laparotomy group. As for the postoperative parameters, the robotic group showed reduced postoperative and 24-hour pain scores, shortened length of hospital stay, and decreased time to full diet resumption compared with the other 2 surgical groups. No significant differences were found between the groups in perioperative complication rate or disease-free survival. Conclusions: The data suggested that robotic surgery is a feasible and potentially optimal option for the treatment of stage IA to IIB cervical cancer with favorable short-term surgical outcomes.